Effect of (Joyce & Weil) and (JJK) in the skills of students - Ahmed Alamiry, Zainab Aziz (Opción, 2019)
The research aims to identify the effectiveness of the strategies (Joyce & Weil) and Jay (JK) via a constructed objective test of the classification skills of the multiple choice type. As a result, the calculated T value is greater than the scale, and the difference is statistically significant for the first experimental group in the average post-test scores of the classification skills. In conclusion, Students desire to learn the best methods according to the steps of the strategy in the presence of a teacher facilitator and organizer of the educational process where crystallized chemical concepts in their minds.